Analyzing grammar errors among Hellotalk users and proposing effective correction strategies - Arifin, Muhammad Nur; Heriyanto, Eko; Kurniadi, Didit; Arvianti, Indah (Universitas Muhammadiyah Malang, 2024)
HelloTalk is a popular social media platform where users from diverse linguistic backgrounds converge to communicate and improve their second language (L2) skills. This study focuses on grammatical errors made by users on the HelloTalk app during English interactions. Employing the observation method. Employing a qualitative approach, the study conducted a comprehensive analysis of 357 instances across 280 posts, showcasing a nuanced understanding of the challenges faced by users in their language learning journey. The identified strategies for addressing these errors encompasses several ways such as providing corrective feedback (CF), categorizing errors, utilizing language learning apps for English, and implementing a systematic approach to monitoring and tracking progress. The study's findings provided valuable insights for educators, language learners, and app developers, offering a basis for targeted interventions. Additionally, future research may explore integrating emerging technologies like artificial intelligence and natural language processing to enhance error correction efficiency and personalized feedback on language learning platforms.